Gap Junctions pada Ischemia-Related Ventrikel Aritmia - Berlian Idriansyah Idris; Yoga Yuniadi (The Indonesian Heart Association, 2011)
Cardiovascular diseases are the leading cause of death worldwide, with isch-emic heart disease being the most common entity. Ventricular arrhythmia is one of the complications of ischemia that can result in sudden cardiac death. One of the underlying mechanisms of ischemia induced arrhythmia is closure of cardiac myocytes gap junctions, where gap junctions are channel-like structure between cells that allow passage of molecules and electrical current. During ischemia, gap junctions close incompletely, creating tissue impedance heterogeneity and conduction slowing, which provide substrate for ventricular arrhythmia. Conditions where gap junctions structure is altered, such as in heart failure, is associated with increased vulnerability of ischemia-induced ventricular arrhythmia.